Moderno descoberto por filmes que pensam o cinema de Lumière ao pós-guerra - Pedrosa, Leonardo Bomfim (2012)
The goal of this research is to find the modern possibilities signalized by Cinema, itself, along the period that runs from its appearance, with Louis Lumière in 1895, until the representation crisis in the post-war period, marked by the oeuvre of filmmakers such as Orson Welles, Alfred Hitchcock and Jean Renoir. Via this research, we aim to have a better understanding of the ways in which the idea of 'modern' in films encounters the realist essence imposed by various theorists, such as Ricciotto Canudo and André Bazin, on the theme.